Total Mechanical Intestinal Obstruction Due to Ascaris Ball in Adolescents: A Case Report - Andly Resando Mallo; Ajeng Purwasih Sutomo; Jeremy Gerald Setiamidjaja; Yunilda Sianipar; Shifa Farahdilla Tifarin (Riviera Publishing, 2026)
Intestinal worm infections remain a health problem in developing countries, especially in areas with poor sanitation. Ascaris lumbricoides is one of the causes of helminth infections that can lead to serious complications, such as intestinal obstruction. This research aims to report cases of intestinal obstruction due to an Ascaris ball in adolescent patients. The method used was a case report on a 14-year-old female patient who was treated for six days with the main complaint of pain all over the abdomen, accompanied by vomiting containing worms. Physical examination showed abdominal tenderness and decreased intestinal sounds, while laboratory examination showed leukocytosis. Radiological examination revealed meteorism. The patient was diagnosed with abdominal pain secondary to ascariasis with suspected partial ileal obstruction due to the Ascaris ball. Initial therapy included intravenous fluids, antibiotics, antiemetics, analgesics, and albendazole. However, due to a total mechanical intestinal obstruction, an exploratory laparotomy was performed. During surgery, dilation of the jejunum and obstruction of the ileum were found to be caused by a collection of worms resembling a ball. Hundreds of worms were evacuated from the intestinal lumen, and intestinal flushing was carried out. The patient showed improvement in her condition after surgery and follow-up therapy. This case demonstrates that ascariasis infection can cause serious complications, such as intestinal obstruction, that require surgery. Early diagnosis and proper management are essential to prevent more severe complications.